2018
DOI: 10.5387/fms.2017-20
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative neck symptoms of posterior approach for cervical compressive myelopathy: Expansive open-door laminoplasty vs. segmental partial laminectomy

Abstract: SPL seems to be a better procedure for reducing postoperative neck symptoms, when compared with C3-C7 ELAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The spine surgeon usually divides the muscles with the exception of the platysma and the omohyoid, which can be transected, and the longus colli that normally are detached from the anterior surface of the cervical spine. In posterior approaches, the posterior paraspinal muscles are detached from the spine in order to gain access to underlying significant anatomical structures such as the spinous process, the laminae, the facets, the pedicles, the neuronal foramens, the vertebrae, the spinal canal and the spinal cord [36][37][38][39][40][41][42][43][44]. The degree of detachment depends on the pathology and the type of the procedure (laminectomy/laminectomies, foraminotomies, posterior fusion with screws and rods, etc).…”
Section: Discussionmentioning
confidence: 99%
“…The spine surgeon usually divides the muscles with the exception of the platysma and the omohyoid, which can be transected, and the longus colli that normally are detached from the anterior surface of the cervical spine. In posterior approaches, the posterior paraspinal muscles are detached from the spine in order to gain access to underlying significant anatomical structures such as the spinous process, the laminae, the facets, the pedicles, the neuronal foramens, the vertebrae, the spinal canal and the spinal cord [36][37][38][39][40][41][42][43][44]. The degree of detachment depends on the pathology and the type of the procedure (laminectomy/laminectomies, foraminotomies, posterior fusion with screws and rods, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Laminoplasty is much more tissue sparing than laminectomy and preserves motion relatively well. It allows reconstruction of cervical lordosis without fusion [16]. Nowadays laminoplasty has become the Figure 2.…”
Section: Posterior Cervical Approachesmentioning
confidence: 99%
“…In both techniques the opening can be maintained by using a bone graft, ceramic spacers, or plates [5,11,14]. Possible complications include: loss of cervical lordosis, decreased cervical range of motion (17-20%), axial neck pain (40-60%), dural tear with cerebrospinal fluid leakage, C5 nerve root palsy (5-12%), infection (3-4%), and potential progression of ossification of posterior longitudinal ligament [4,8,11,16]. The latest research has shown that preservation of the C2 and C7 muscular attachments can prevent post-surgical axial neck pain and reduced range of cervical motion [5,16].…”
Section: Posterior Cervical Approachesmentioning
confidence: 99%